2020
DOI: 10.3390/agronomy10091294
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Melting and Insertion Site-Based Polymorphism Markers for Wheat Variability Analysis and Candidate Genes Selection at Drought and Heat MQTL Loci

Abstract: The practical use of molecular markers is facilitated by cost-effective detection techniques. In this work, wheat insertion site-based polymorphisms (ISBP) markers were set up for genotyping using high-resolution melting analysis (HRM). Polymorphic HRM-ISBP assays were developed for wheat chromosomes 4A and 3B and used for wheat variability assessment. The marker sequences were mapped against the wheat genome reference sequence, targeting interesting genes. Those genes were located within or in proximity to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 120 publications
(193 reference statements)
0
16
0
Order By: Relevance
“…Further, Mérida-García et al 2020reported candidate genes underpinning metaQTL reported by Acuña-Galindo et al 2015on chromosomes 3B and 4A. The candidate genes reported here ( Supplementary Table 6) with proven roles in abiotic stress tolerance in model crops or having expression evidences in wheat under various stress conditions expand opportunities for future validation studies (Mérida-García et al, 2020).…”
Section: Discussionmentioning
confidence: 63%
“…Further, Mérida-García et al 2020reported candidate genes underpinning metaQTL reported by Acuña-Galindo et al 2015on chromosomes 3B and 4A. The candidate genes reported here ( Supplementary Table 6) with proven roles in abiotic stress tolerance in model crops or having expression evidences in wheat under various stress conditions expand opportunities for future validation studies (Mérida-García et al, 2020).…”
Section: Discussionmentioning
confidence: 63%
“…Genetic diversity is crucial for crop improvement, as it allow breeders to identify appropriate parents to be included in breeding programs for broadening genetic variability. Within this Special Issue, the genetic diversity of wheat, avocado, and raspberry was assessed by high-resolution melting (HRM), and insertion site-based polymorphism (ISBP) markers, simple sequence repeats (SSR) developed from single-molecule long-read sequences, and SSRs from flavonoid biosynthesis genes, respectively [14][15][16]. Merida-Garcia et al [14] developed ISBP markers for the wheat genome as an alternative to SSRs and SNPs.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…Within this Special Issue, the genetic diversity of wheat, avocado, and raspberry was assessed by high-resolution melting (HRM), and insertion site-based polymorphism (ISBP) markers, simple sequence repeats (SSR) developed from single-molecule long-read sequences, and SSRs from flavonoid biosynthesis genes, respectively [14][15][16]. Merida-Garcia et al [14] developed ISBP markers for the wheat genome as an alternative to SSRs and SNPs. The authors concluded that these HRM-ISBPs are a cost-effective and efficient marker approach for wheat breeding programs, being also useful for gene tagging.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…As result, tolerance to these abiotic stresses are important aims in plant breeding to increase crops production [8]. In this way, molecular markers as ISBP, can be developed and applied to identify genomic regions and genes of interest closely related to interesting traits as drought and heat tolerance [9]. ISBP are PCR markers designed based on the information of sequence flanking TE sequences [10].…”
Section: Introductionmentioning
confidence: 99%
“…They appeared as powerful and interesting tools to apply in genomic and genetic studies in wheat [10][11][12], and have been also used in marker-assisted selection (MAS) and as selecting tools in plant breeding programs [10]. These markers have been designed for several wheat chromosomes [9,11,[13][14][15][16] and applied with different aims [17][18][19][20][21]. Mérida-García et al [9] developed HRM assays based on ISBP markers for wheat chromosomes 4A and 3B.…”
Section: Introductionmentioning
confidence: 99%